Chemically induced repair, adhesion, and recycling of polymers made by inverse vulcanization. Issue 21 (20th May 2020) - Tonkin, Samuel J.; Gibson, Christopher T.; Campbell, Jonathan A.; Lewis, David A.; Karton, Amir; Hasell, Tom; Chalker, Justin M.
Abstract : Polymers made by inverse vulcanization can be assembled, repaired, and recycled at room temperature through nucleophile-catalyzed S–S metathesis. Abstract : Inverse vulcanization is a copolymerization of elemental sulfur and alkenes that provides unique materials with high sulfur content (typically ≥50% sulfur by mass). These polymers contain a dynamic and reactive polysulfide network that creates many opportunities for processing, assembly, and repair that are not possible with traditional plastics, rubbers and thermosets. In this study, we demonstrate that two surfaces of these sulfur polymers can be chemically joined at room temperature through a phosphine or amine-catalyzed exchange of the S–S bonds in the polymer. When the nucleophile is pyridine or triethylamine, we show that S–S metathesis only occurs at room temperature for a sulfur rank > 2—an important discovery for the design of polymers made by inverse vulcanization. This mechanistic understanding of the S–S metathesis was further supported with small molecule crossover experiments in addition to computational studies. Applications of this chemistry in latent adhesives, additive manufacturing, polymer repair, and recycling are also presented.